If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = t(20 + -4.9t) 2 = (20 * t + -4.9t * t) 2 = (20t + -4.9t2) Solving 2 = 20t + -4.9t2 Solving for variable 't'. Reorder the terms: 2 + -20t + 4.9t2 = 20t + -20t + -4.9t2 + 4.9t2 Combine like terms: 20t + -20t = 0 2 + -20t + 4.9t2 = 0 + -4.9t2 + 4.9t2 2 + -20t + 4.9t2 = -4.9t2 + 4.9t2 Combine like terms: -4.9t2 + 4.9t2 = 0.0 2 + -20t + 4.9t2 = 0.0 Begin completing the square. Divide all terms by 4.9 the coefficient of the squared term: Divide each side by '4.9'. 0.4081632653 + -4.081632653t + t2 = 0 Move the constant term to the right: Add '-0.4081632653' to each side of the equation. 0.4081632653 + -4.081632653t + -0.4081632653 + t2 = 0 + -0.4081632653 Reorder the terms: 0.4081632653 + -0.4081632653 + -4.081632653t + t2 = 0 + -0.4081632653 Combine like terms: 0.4081632653 + -0.4081632653 = 0.0000000000 0.0000000000 + -4.081632653t + t2 = 0 + -0.4081632653 -4.081632653t + t2 = 0 + -0.4081632653 Combine like terms: 0 + -0.4081632653 = -0.4081632653 -4.081632653t + t2 = -0.4081632653 The t term is -4.081632653t. Take half its coefficient (-2.040816327). Square it (4.164931281) and add it to both sides. Add '4.164931281' to each side of the equation. -4.081632653t + 4.164931281 + t2 = -0.4081632653 + 4.164931281 Reorder the terms: 4.164931281 + -4.081632653t + t2 = -0.4081632653 + 4.164931281 Combine like terms: -0.4081632653 + 4.164931281 = 3.7567680157 4.164931281 + -4.081632653t + t2 = 3.7567680157 Factor a perfect square on the left side: (t + -2.040816327)(t + -2.040816327) = 3.7567680157 Calculate the square root of the right side: 1.938238379 Break this problem into two subproblems by setting (t + -2.040816327) equal to 1.938238379 and -1.938238379.Subproblem 1
t + -2.040816327 = 1.938238379 Simplifying t + -2.040816327 = 1.938238379 Reorder the terms: -2.040816327 + t = 1.938238379 Solving -2.040816327 + t = 1.938238379 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2.040816327' to each side of the equation. -2.040816327 + 2.040816327 + t = 1.938238379 + 2.040816327 Combine like terms: -2.040816327 + 2.040816327 = 0.000000000 0.000000000 + t = 1.938238379 + 2.040816327 t = 1.938238379 + 2.040816327 Combine like terms: 1.938238379 + 2.040816327 = 3.979054706 t = 3.979054706 Simplifying t = 3.979054706Subproblem 2
t + -2.040816327 = -1.938238379 Simplifying t + -2.040816327 = -1.938238379 Reorder the terms: -2.040816327 + t = -1.938238379 Solving -2.040816327 + t = -1.938238379 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2.040816327' to each side of the equation. -2.040816327 + 2.040816327 + t = -1.938238379 + 2.040816327 Combine like terms: -2.040816327 + 2.040816327 = 0.000000000 0.000000000 + t = -1.938238379 + 2.040816327 t = -1.938238379 + 2.040816327 Combine like terms: -1.938238379 + 2.040816327 = 0.102577948 t = 0.102577948 Simplifying t = 0.102577948Solution
The solution to the problem is based on the solutions from the subproblems. t = {3.979054706, 0.102577948}
| 6x+7=7x+6 | | 8x-52=2x+14 | | x^2-72x+256=0 | | 180=108(x+18) | | (12+8x)=1 | | (7+3i)-(2+3i)= | | 3y+3x-2=7 | | 1n+9n-10-3= | | 7(9x-3)=4(3x+2) | | 148-4x=60 | | (12-8x)=1 | | 4x-18+x^2-7x=10 | | 7(x+11)=18x+22 | | -2(d+4)-d-3=-3(d+5)+4 | | (5-i)(5+i)= | | -3.2(30)=-96 | | x^2-4x+1=k(x-4) | | x+2y+2z=-1 | | 3m-42-12+12=24 | | 3x+21=5 | | 7(n-8)-(6-n)= | | (3-i)+(1-2i)= | | 9x+12=15x-24 | | v/8=14 | | 95-7x=60 | | 5+5=10+10x | | 10(4-3i)= | | -3.2a=-96 | | 7y-168=3y | | 81r-48rt=0 | | 2a^2+11a=-5 | | w/12=9 |